A imigração italiana no desenvolvimento do município de Rio Claro - SP: economia e cultura (1870-1950) - Meirelles, Adriano Carlos [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
In the second half of the nineteenth century, Brazil received a huge number of European immigrants, mostly Portuguese, Spanish and Italian. In the southern and southeastern Italian immigration was the great alternative to replace the slave labor that was already decreasing since 1850 to ban the slave trade. The state of São Paulo received most of the Italian immigrants's families who were working in the coffee harvest mainly in the system that became known as settlement. Some families or single ItaIians moved to the city after some time. In Rio Claro the consequence of the immigration process has brought significant positive influence to the city due to the combination coffeerailroad-immigrant which leveraged its growth and development. This study will address the historical issues of immigration to Rio Claro, analyzing the local and regional context of the second half of the nineteenth century and the first half of the twentieth century. Emphasizing that the Italian families mainly represented what the contributions were, the legacy left in the social, economic, cultural, sportive, educational and religious

Na segunda metade do século XIX, o Brasil recebeu um gigantesco número de imigrantes europeus, principalmente portugueses, espanhóis e italianos. Na região sul e sudeste a imigração italiana foi a grande alternativa para substituir a mão de obra escrava que já estava diminuindo desde 1850 com a proibição do tráfico negreiro. O estado de São Paulo recebeu a maior parte das famílias de imigrantes italianos que foram trabalhar na colheita do café principalmente, no sistema que ficou conhecido por colonato. Algumas famílias ou italianos solteiros partiam para cidade depois de algum tempo. Em Rio Claro a consequência do processo de imigração trouxe influencias significativamente positivas para a cidade, devido à combinação café-ferroviaimigrante que alavancava o crescimento e desenvolvimento. Nesse estudo abordaremos as questões históricas da imigração para Rio Claro, analisando o contexto local e regional da segunda metade do século XIX e primeira metade do século XX. Enfatizando o que as famílias italianas principalmente, representaram, quais foram as contribuições, o legado deixado no desenvolvimento social, econômico, cultural, esportivo, educacional e religioso
Keywords: Imigrantes; Italianos; Economia; Cultura; Café; Ferrovias; Brasil - Migração - 1870-1950; Rio Claro (SP) - Séc. XIX